FACTORS THAT CAUSE OF LAND CONVERSION TO THE INCREASING OF FLOODING RISK IN MANGGALA SUB-DISTRICT, MAKASSAR - Adhe Reza Rachmat; Adjie Pamungkas; Rimadewi Suprihardjo (Journal of Architecture&ENVIRONMENT, 2015)
Flooding that occurred in Manggala Sub-district gave negative impact to the community in the form of material loss and disruption of community activities. This condition was caused by vulnerable landscapes and inadequate drainage systems. Besides, it was caused by the high rate of construction growth phenomenon. The phenomenon led to the conversion of agricultural land and green open space into residential. Consequently, it emerged insistence on drainage and infiltration capacity of the soil to the surface water runoff, thus increasing the risk of flooding in Manggala Sub-District. Therefore, this study aimed to determine the factors that cause of land conversion triggering an impact in increasing of flooding risk in Manggala Sub-district. This article is a part of research on the formulation the concept of controlling spatial utilization in improving the resilience of city against flooding in the Manggala Sub-District, Makassar. Through Content Analysis technique, the variables that cause of land conversion to the increasing of flooding risk were found. The results showed that there were 4 (four) factors. That causes of land conversion in Manggala Sub-district: the lack of planning and law enforcement related to spatial planning; high demand for housing; the low price of open land; the uneven and partial of infrastructure’s supply.